THE DYNAMICS OF LACK AND DESIRE IN OLIVIA RODRIGO'S GUTS ALBUM - Maula, Jechan Shofwatul; Nurrachman, Dian; Permanaludin, Udayani (Universitas Islam Sumatera Utara (UISU), 2025)
This research examines the dynamics of “lack” and “desire” in Olivia Rodrigo's Guts album through an expressive literary criticism approach based on Lacanian psychoanalysis. Using close reading, this study uncovers how the lyrics reflect the subject’s confrontation with existential emptiness (lack) and the pursuit of an unattainable objet petit a, shaped by the symbolic Other (language, social norms). Thematic patterns such as emotional vulnerability, self-doubt, and resistance to societal expectations demonstrate how desire arises not from personal will but through the mediation of external pressures. The lyrics portray a cycle where the subject’s yearning is constantly frustrated by the impossibility of fully attaining the desired object, highlighting the persistent experience of lack. This tension reveals the paradox of desire as both motivating and destabilizing, showing how identity is fragmented by conflicting demands of the self and the Other. By linking these thematic motifs to Lacanian concepts, the research concretely illustrates the psychological and social dynamics at play, offering new insights into contemporary youth identity in digital culture.